Adriatic coast of Croatia and its hinterland from 50, 000 to 25, 000 BP - Karavanić, Ivor (Array, 2005)
The paper presents recent analysis of the artifacts from upper levels with Mousterian industry at Mujina Pećina, Dalmatia and Aurignacian levels od Šandalja II, Istria. Mousterian tools in Mujina Pećina are produced on locaj chert, occasionally using Levallois technology. Local chert in also predominant in Aurignacian of Šandalja II where blades are produced with soft hammer. Beside Mujina Pećina (cave), there are many Mousterian open air sites in Dalmatia, while Aurignacian sites on Adriatic coast of Croatia are very rare. Possible explanation could be sea level rising at the end of the Pleistocene or scarcely populated coast during Aurignacian.